MEDICAL ERROR: HISTORICALLY-LEGAL ASPECT - Savchenko, V.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
From ancient times of people surrounded illnesses. In attempt of healing they addressed to people. With the advent of the first doctors there was a question, on their responsibility. People were ready to give all property for the sake of healing. But what to do with the doctor if he has made the mistake which has entailed deterioration of health or death. Certain cultures and the people, operated differently. The institute of responsibility of medical workers developed, evolved, incorporating principles of the past and creating the new.